LITERASI INFORMASI MANAJEMEN KESEHATAN PERIKANAN - Doni Darmasetiadi; Ricko Reynalta (JURNAL RISET RUMPUN ILMU HEWANI, 2023)
This article contains information literacy related to fish health management. This writing was conducted by means of a literature study. This paper focuses on the ability of fishermen and fish cultivators to be able to find appropriate information related to fish health management and efforts to prevent fish disease. In this article, the conceptual meaning of information literacy and fish health management is carried out. Next, the discussion is carried out with the elaboration between the two concepts. The results of the discussion found that fish health management requires a process whereby understanding the right information, the right source of information, and comparing the information to be decided to take. Fish health management information literacy is important for fishermen and fish farmers. fishermen and fish cultivators can independently and accompanied find the information needed related to fish health management information and how to prevent disease in fish.